The effect of accountant reputation on initial public offerings in Malaysia - Ong, Tze San; Teh, Boon Heng; Yap, Voon Choong (Indian Institute of Economics, 2010)
This paper assesses the characteristics and the influence of accountants’ reputations on the underpricing of Initial Public Offerings (IPOs) stocks listed in the Main Board and Second Board of the Malaysia Stock Market. The sample data comprises of the first day price and the issue price of IPOs stocks selected from the financial year of 2005, 2006 and 2008. Results showed that there is a significant positive first day return, indicating a certain degree of underpricing in the IPOs stocks. However, there are no significant differences for returns, risks and coefficient of variation among the two groups of IPOs stocks audited respectively by the Big Four and non Big Four accounting firms. That is, IPOs stocks performance in terms of initial first day returns are not influenced by the factor accountants’ reputations.